KEANEKARAGAMAN MIKROALGA DI AIR TERJUN SANDO, KOTA LUBUKLINGGAU, SUMATRA SELATAN - Harmoko, Harmoko; Lokaria, Eka; Anggraini, Resti (Research Center for Limnology, 2019)
There is still a little exploration of biodiversity in Lubuklinggau City, one of which is on microalgae. This study aimed to determine the biodiversity of microalgae found in Sando Waterfall. This study used survey techniques, and was carried out in June?July 2017 in Sando Waterfall, Lubuklinggau Barat I District in Lubuklinggau City. Sampling was carried out in the morning at three stations with three replications. Data were collected by observing the microalgae using a microscope and were then analyzed descriptively and qualitatively. The results showed that microalgae found in Sando Waterfall consisted of 4 divisions which are Bacillariophyta, Charophyta, Chlorophyta, dan Cyanophyta. A total of 27 genera and 30 species were found, namely Closterium sp., Cosmarium sp., Micrasterias sp., Oocystis sp., Desmidium sp., Actinastrum sp., Carteria sp., Ulothrix sp., Microspora sp., Spirogyra sp., Oedogonium sp., Euastrum sp., Xanthidium sp., Navicula sp., Asterionella sp., Eunotia sp., Cyclotella sp., Melosira sp., Guinardia sp., Surirella sp., Surirella elegans, Synedra sp., Synedra ulna, Pleurosigma directum, Fragillaria sp., Tabellaria flocculosa, Nitschia sp., Oscillatoria sp., Oscillatoria limosa, and Lyngbya sp. The most dominant division found in Sando Waterfall was Bacillariophyta which also has the highest number of species. There were five species most commonly found in Sando Waterfall, which are also members of the Bacillariophyta division, namely Navicula sp., Eunotia sp., Melosira sp., Surirella sp., and Fragillaria sp. This finding is thought to be related to the adaptability of these species to strong current of water which is the ecological condition of waterfalls. Water qualities measured in this study were the water temperature of 27°C, the pH value of 7.2, the clarity of 37 cm, and the dissolved oxygen concentration of 32 mg/L. These conditions supported the life of microalgae in Sando Waterfall.